To solve for \( 2C + 3D \) using the given expressions for \( C \) and \( D \), we begin by substituting the values of \( C \) and \( D \).
-
The expression for \( C \) is given as: \[ C = x + 8 \]
-
The expression for \( D \) is given as: \[ D = 2x + 10 \]
Now we will calculate \( 2C \) and \( 3D \):
Step 1: Calculate \( 2C \)
\[ 2C = 2(x + 8) = 2x + 16 \]
Step 2: Calculate \( 3D \)
\[ 3D = 3(2x + 10) = 6x + 30 \]
Step 3: Combine \( 2C \) and \( 3D \)
Now we can find \( 2C + 3D \): \[ 2C + 3D = (2x + 16) + (6x + 30) \]
Combine like terms: \[ 2C + 3D = 2x + 6x + 16 + 30 = 8x + 46 \]
Final Expression
Thus, the expression \( 2C + 3D \) in standard form is: \[ \boxed{8x + 46} \]